Adult intrarenal neuroblastoma presenting as renal cell carcinoma - Bayrak, Omer; Seckiner, Ilker; Erturhan, Sakip; Aydin, Abdullah; Yagci, Faruk (Canadian Urological Association Journal, 2013)
Neuroblastoma is known to arise from cells of the neural crest that form the adrenal medulla and sympathetic ganglia. Tumours may occur anywhere along the sympathetic chain within neck, thorax, retroperitoneum, pelvis or in the adrenal gland. Seventy-five percent arise in the retroperitoneum, 50% in the adrenal, and 25% in the paravertebral ganglia.1 The variety of locations in which these tumours can arise and the spectrum of their differentiation result in a wide range of clinical presentations and behaviours. These tumours can undergo spontaneous regression, differentiate to benign neoplasm or exhibit extremely malignant behaviour. Neuroblastoma has a variable prognosis and is very rarely reported in adults. There are only 3 cases in the English literature on kidney neuroblastoma. We present a case of neuroblastoma in a woman who had an intrarenal mass.